Gender considerations in One Health: a framework for researchers - Galiè, Alessandra; McLeod, Anni; Campbell, Zoë A.; Ngwili, Nicholas; Terfa, Zelalem G.; Thomas, Lian F. (Frontiers in Public Health, 2024)
One Health research and intervention outcomes are strongly influenced by gender dynamics. Women, men, girls, and boys can be negatively affected by gender-based disadvantage in any of the three One Health domains (animal, human, and environmental health), and where this occurs in more than one domain the result may be a compounding of inequity. Evidence worldwide shows that women and girls are more likely to suffer from such gender-based disadvantage. A thoughtfully implemented One Health intervention that prioritizes gender equity is more likely to be adopted, has fewer unintended negative consequences, and can support progress toward gender equality, however there is limited evidence and discussion to guide using a gender lens in One Health activities. We propose a framework to identify key gender considerations in One Health research for development – with a focus on Low-and Middle-Income Countries. The framework encourages developing two types of research questions at multiple stages of the research process: those with a bioscience entry-point and those with a gender entry-point. Gender considerations at each stage of research, institutional support required, and intervention approaches is described in the framework. We also give an applied example of the framework as it might be used in One Health research. Incorporation of gender questions in One Health research supports progress toward more equitable, sustainable, and effective One Health interventions. We hope that this framework will be implemented and optimized for use across many One Health challenge areas with the goal of mainstreaming gender into One Health research.